Cigarette Smoking and Betel Nut Chewing Behavior among Junior High School Students in Rural Sorong, West Papua, Indonesia - Jamal Zaini; Siti Syahral Ain; Samuel Sidang Kamalle; Astrid Brilianty Putri Rase; Simon Sampe; Andrade Monteiro (Jurnal Respirasi, 2026)
Introduction: Smoking and other unhealthy behaviors, such as betel nut chewing, alcohol consumption, and vaping, are potential health problems in the eastern part of Indonesia. It is prevalent among young adolescents in Eastern Indonesia. Nevertheless, data regarding these are still rare, especially among rural Papua residents. This study aimed to examine health-impacting behaviors, such as smoking and betel nut chewing, among junior high school students in rural Sorong, West Papua, Indonesia. This study also evaluated the correlation between the adolescent’s knowledge about the dangers of smoking and smoking behavior. Methods: This study was conducted at a public junior high school in the Klamono District, rural Sorong, West Papua, Indonesia. All subjects completed the questionnaire using the Indonesian version of the Global Youth Tobacco Survey (GYTS). Results: The prevalence of cigarette smoking (29.7%), betel nut chewing (64.4%), alcohol drinking (14.4%), and vaping behavior (10.2%) among subjects was high. This study also showed a correlation between students’ knowledge about the dangers of smoking and smoking behavior. Conclusion: Cigarette smoking, betel nut chewing, alcohol drinking, and vaping were high among junior high school students in rural Sorong, West Papua, Indonesia, and could pose potential health problems in the future.